Role of Saccharomyces boulardii and Bacillus clausii in reducing the duration of diarrhea: a three-armed randomised controlled trial - D., Vidjeadevan; S., Vinoth; S., Ramesh (International Journal of Contemporary Pediatrics, 2018)
Background: Diarrhea is a major public health problem. Probiotics have been recommended as an add-on therapy for the treatment of diarrhea. Recently Saccharomyces boulardii and Bacillus clausii, yeast and spore forming bacilli are among the probiotics in use for diarrheal disorder. Methods: This was a three armed randomised controlled trial conducted in pediatrics department, in a tertiary level care at Chidambaram. The randomisation was done using permuted blocks method. Of the three groups, Group A received ORS and zinc; Group B ORS, zinc and S. boulardii and Group C ORS, zinc and B. clausii. The outcome variables included duration of diarrhea and duration of stay in hospital. Results: The duration of diarrhea decreased significantly in Group B and C than Group A. Both the probiotics had similar effect in reducing the duration of diarrhea. There was no significant difference in duration of stay at hospital between the groups. Conclusions: Addition of probiotics as an add-on therapy would aid in decreasing the duration of diarrhea rather than giving ORS and zinc alone. The duration of stay in hospital was unaffected by the change in regimen of treatment.